Атмосфера как коллоидная система - Гончарук, В.В.; Лапшин, В.Б.; Чичаева, М.А.; Сыроешкин, А.В. (Химия и технология воды, 2011)
В работе рассмотрены состав и механизмы формирования атмосферного аэрозоля. Описаны оптические явления в атмосфере, обусловленные её коллоидными свойствами. Особое внимание уделено морскому аэрозолю в приводном слое атмосферы и его токсичности. В роботі розглянуто склад і механізми формування атмосферного аерозолю. Описано оптичні явища в атмосфері, обумовлені її колоїдними властивостями. Особливу увагу приділено морському аерозолю в приводному шарі атмосфери і його токсичності. Atmosphere is a layer of gases around the Earth, which stretches from the Earth ground up to 100 km height, where it gradually transforms into the space environment. In the Article the atmosphere is regarded as a system containing a disperse phase, which possesses a wide range of processes and features that can be explained within the examination of atmosphere as colloidal system. The Article explains the effects that are related to the atmosphere‘s dispersion feature.